Drone journalism: praktiknya dalam foto jurnalistik di Indonesia (Faculty of Communications Science, Dr. Soetomo University, 2022)
One of the most recent visual news gathering is the use of Unmanned Aerial Vehicles (UAVs) or drones. The use of drones for reporting is increasing as drone technology is getting cheaper. The use of drones also takes place in Indonesia, one of which is in photojournalism. This study focuses on the use of drones in the practice of photojournalism in Indonesia by using a purposive sampling method in which in-depth interviews are conducted. The trend of drone is tested using interviews and other additional evidence including document studies and observations, in how high-altitude photography is becoming a new requirement for photojournalists' work and how its ethical and regulatory aspects. The findings of this paper will help photojournalists and media to spot trends and adapt to the visual needs of the media they work for Keywords: Drone, Unmanned Aerial Vehicles, Drone Journalism, Photojournalism.